Design, fabrication and evaluation of novel SIS based regenerative vascular grafts for hemodialysis access (2018)
"Chronic kidney disease (CKD) needs improved therapy options to ensure better quality of life for patients. Since kidneys are not easily available for each patient, renal replacement therapies are still necessary to remove waste from the blood, as a healthy kidney would do. Hemodialysis being one of the most common long-term treatments for CKD, is in the need of a vascular access, an arteriovenous connection currently made with synthetic materials as expanded polytetrafluoroethylene (ePTFE), that have important complications as intimal hyperplasia, infection and thrombosis, due to the chemical, biological and mechanical properties when compared to native blood vessels of the patients. To face complications of current ePTFE vascular grafts, in this study small intestinal submucosa (SIS) was decellularized and carefully rolled to manufacture flexible C-shaped vascular grafts, four millimeters of diameter, capable to restrain arterial flow without any kink or complication in the arterial and venous anastomosis. Even if patency rates and regeneration were superior in SIS based vascular grafts than ePTFE, thrombosis remained as the main complication during the maturation process. To reduce thrombogenesis, three carboxyl-terminated macromolecules with different molecular weights were conjugated to the pendant amine groups on the SIS surface: zwitterionic phosphorylcholine, carboxylic acids and polyethylene glycol. Reduction in platelet deposition was significant with carboxylic acids, but remarkable with zwitterionic macromolecules of Phosphorylcholine, and even better with Polyethylene Glycol. PEGylation of SIS was easy, cheap, and even with a low conjugation yield, improved the SIS mechanical properties making SIS vascular grafts significantly like native arteries, without altering the biocompatible regenerative properties of the SIS. Results obtained in this thesis show the SIS capability to adapt to different conditions, remaining as an excellent scaffold for different."--Tomado del Formato de Documento de Grado